Poor Seizure Control Among Children Attending a Tertiary Hospital in South Western Uganda – A Retrospective Study - Namusisi, Jane; Kyoyagala, Stella; Nantongo, Josephine; Kyewalyanga, Mike; Sabiiti, Stephen; Murorunkwere, Angelique; Najjuma, Josephine Nambi; Nakibuuka, Jane; Kaddumukasa, Mark; Sajatovic, Martha; Kalubi, Peter (International Journal of General Medicine, 2023)
Background: Seizure control among children with epilepsy (CWE) receiving anti-seizure medications (ASMs) remains a challenge in low-resource settings. Uncontrolled seizures are significantly associated with increased morbidity and mortality among CWE. This negatively impacts their quality of life and increases stigma. Aim: This study determined seizure control status and described the factors associated among CWE receiving ASMs at Mbarara Regional Referral Hospital (MRRH). Methods: In a retrospective chart review study, socio-demographic and clinical data were obtained from 112 medical records. CWE receiving ASMs for at least six months and regularly attending the clinic were included in the study. Physical or telephone interviews were conducted with the immediate caregivers of the CWE to establish the current seizure control status of the participants. Results: A total of 112 participants were enrolled. Of these, three-quarters had generalized onset seizures, 23% had focal onset seizures, while 2% had unknown onset motor seizures. About 60.4% of the study participants had poor seizure control. Having a comorbidity (p-value 0.048, AOR 3.2 (95% CI 1.0–9.9)), history suggestive of birth asphyxia (p-value 0.014, AOR 17.8 (95% CI 1.8–176.8)), and being an adolescent (p-value 0.006, AOR 6.8 (95% CI 1.8–26.6)) were significantly associated with poor seizure control. Conclusion: Seizure control among CWE receiving ASMs at MRRH remains poor. Efforts geared to addressing seizure control and optimizing drugs are needed, especially among children with comorbidities, those with history of birth asphyxia, and adolescents
Keywords: Epilepsy; Anti-seizure medications; Children; Seizure control; Uganda